A prospective multicenter study on prognostic factors and quality of care in Severe Acquired Brain Injury rehabilitation units: a project from the Tiresia network - Nattino, Giovanni; Acler, Michele; Bargellesi, Stefano; Bertagnoni, Giannettore; Carrara, Greta; De Tanti, Antonio; Estraneo, Anna; Ghilardi, Giulia Irene; Lavezzi, Susanna; Lombardi, Francesco; Lucca, Lucia Francesca; Mancuso, Mauro; et al. (Frontiers in Neurology, 2025)
BackgroundSevere Acquired Brain Injury (sABI) presents significant challenges in clinical management and rehabilitation due to its diverse and complex nature. The primary objective of the Tiresia project is to identify medium and medium-to-long-term prognostic factors for patients with sABI and to develop outcome indicators to evaluate the quality of care in rehabilitation units.MethodsThis paper outlines the protocol for a prospective observational multicenter study conducted within the Tiresia Network. The study relies on a comprehensive data collection with stringent quality control measures. Ethical considerations emphasize patient privacy protection and adherence to regulatory standards. All of the Italian intensive rehabilitation units dedicated to sABI patients were eligible to participate in the study. Twenty-seven of them joined the project and started the data collection.DiscussionThe present study represents a comprehensive effort to address critical gaps in sABI research and practice through a multicenter, prospective study design. Through rigorous data collection, analysis, and ethical oversight, the Tiresia project endorses the commitment of the research community to advancing evidence-based care and optimizing patient outcomes in sABI rehabilitation.Clinical trial registrationThe study was registered on ClinicalTrials.gov (ID: NCT04905264), on 24 May 2021.